Caries experience among adults in core Sámi areas of Northern Norway - Bongo, Ann Kristine Sara; Brustad, Magritt; Jönsson, Birgitta (Community Dentistry and Oral Epidemiology, 2020)
Objectives - Dental caries is a major oral health problem among indigenous people worldwide, but knowledge on this issue among the indigenous Sámi people in Norway is scarce. The aim of the study was to describe dental caries experience in an adult population in core Sámi areas of Northern Norway and to assess the corresponding associations with socio‐demographic, socioeconomic and oral health‐related behavioural factors. Methods - This cross‐sectional study is based on data from the Dental Health in the North study (2033 participants aged 18‐75 years). A questionnaire was used to collect data on socio‐demographic, socioeconomic and oral health‐related behavioural factors. Clinical examinations were performed by dentists and dental hygienists at Public Dental Service (PDS) clinics in core Sámi areas of Northern Norway. Results - About 68% (n = 1380) of participants reported Sámi ethnicity, and the mean number of decayed (D), missed (M) and filled (F) teeth (T) was 16.2 (standard deviation [SD] = 6.7). The mean DMFT was 15.7 (SD = 6.7) among Sámi and 17.0 (SD = 6.7) among non‐Sámi. The mean DT among Sámi was 1.0 (SD = 1.6), with a significant, higher prevalence among coastal Sámi (DT = 1.3, SD = 1.8) than inland Sámi (DT = 0.8, SD = 1.5). Living in the coastal region, consumption of sugary soft drinks several times a week or daily, toothbrushing less than daily and irregular dental visits were associated with DT. Conclusions - Caries experience among adults in core Sámi areas of Northern Norway was common. Dental caries were more common in the coastal than the inland region, with minor differences in caries experience between Sámi and non‐Sámi people within these regions.